How does social integration influence breast cancer control among urban African-American women? Results from a cross-sectional survey - Washington Carmen; Klassen Ann (BMC, 2008)
Abstract Background Although social integration is a well-established influence on health, less is known about how the specific types of social connection (social roles, social networks, and social support) influence knowledge, attitudes, and practices for specific prevention goals, and how to utilize these influences in interventions with priority populations. This research examined the prevalence of social roles, networks and support among 576 urban African-American women age 45-93 in East Baltimore, Maryland, and the association of these social factors with breast cancer related knowledge, attitudes, and practices. Methods Using data from 1997-1998 in-home interviews, we developed indices of six possible social roles, social networks of family, neighborhood and church, and instrumental and emotional social support. In multivariate models adjusting for age, education, and medical care, we examined the association of each social influence on breast cancer knowledge, attitudes, screening recency and intention, and treatment preferences. Results We found substantial variation in social integration among these women, with social integration positively associated with overall health and well-being. Social roles and networks were positively associated with screening knowledge, and emotional support and church networks were positively associated with attitudes conducive to early detection and treatment. In regard to screening behaviors, family networks were associated with both screening recency and intention. Women with greater church networks and emotional support held more conservative attitudes towards lumpectomy, reconstruction, and clinical trials. Conclusion Overall, social integration is a positive influence on breast cancer control and should be utilized where possible in interventions, including identifying surrogate mechanisms for support for subgroups without existing social resources.